Solid waste: Research and behavioral analysis of students and employees of UFFS - Teilonara Ziliotto, Celsiane; dos Reis, Marcos Roberto (Guará Journal, 2025)
The research consisted of a survey on the opinions and behaviors of the academic community of UFFS on disposal of solid waste on the premises of this. The main objective was to collect and analyze information involving cultural and behavioral aspects, including disposal and solid waste disposal. The means of collecting information was the application of a questionnaire survey and observation. We conclude that the academic community has a regular level of environmental awareness, but situations arise that theoretical knowledge is not brought to the everyday practice, committing waste segregation.
Keywords: Solid waste; Behavioral research; Environmental education